Second language experience modulates word retrieval effort in bilinguals: evidence from pupillometry - Schmidtke, Jens (Frontiers in Psychology, 2014)
Bilingual speakers often have less language experience compared to monolinguals as a result of speaking two languages and/or a later age of acquisition of the second language. This may result in weaker and less precise phonological representations of words in memory, which may cause greater retrieval effort during spoken word recognition. To gauge retrieval effort, the present study compared the effects of word frequency, neighborhood density (ND), and level of English experience by testing monolingual English speakers and native Spanish speakers who differed in their age of acquisition of English (early/late). In the experimental paradigm, participants heard English words and matched them to one of four pictures while the pupil size, an indication of cognitive effort, was recorded. Overall, both frequency and ND effects could be observed in the pupil response, indicating that lower frequency and higher ND were associated with greater retrieval effort. Bilingual speakers showed an overall delayed pupil response and a larger ND effect compared to the monolingual speakers. The frequency effect was the same in early bilinguals and monolinguals but was larger in late bilinguals. Within the group of bilingual speakers, higher English proficiency was associated with an earlier pupil response in addition to a smaller frequency and ND effect. These results suggest that greater retrieval effort associated with bilingualism may be a consequence of reduced language experience rather than constitute a categorical bilingual disadvantage. Future avenues for the use of pupillometry in the field of spoken word recognition are discussed.